2017
DOI: 10.1371/journal.pone.0182511
|View full text |Cite
|
Sign up to set email alerts
|

Overweight/Obesity and associated factors among preschool children in Gondar City, Northwest Ethiopia: A cross-sectional study

Abstract: BackgroundOverweight and obesity among children has emerged as one of the most serious public health concerns in the 21st century, which is a predictor of adulthood obesity, morbidity and mortality. The objective of this study was to assess the prevalence of overweight /obesity and associated factors among preschool children.MethodsA community based cross-sectional study was conducted in Gondar City from February 14 to March 4, 2016. Multi stage sampling technique was used to select a total of 504 preschool ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
83
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 13 publications
17
83
4
Order By: Relevance
“…Younger children had higher odds of becoming overweight or obese than their older counterparts. This is corroborated with studies done in Hawassa, Ethiopia [14], Gondar, Ethiopia [15], Cameroon [16], SSA [9] and Malaysia [17]. This might be explained by the fact that as age of the child increases, the chance to join kindergarten would increase and hence may attribute to increased physical activity which ultimately would lead to increased metabolic activity and energy requirements.…”
Section: Discussionsupporting
confidence: 85%
“…Younger children had higher odds of becoming overweight or obese than their older counterparts. This is corroborated with studies done in Hawassa, Ethiopia [14], Gondar, Ethiopia [15], Cameroon [16], SSA [9] and Malaysia [17]. This might be explained by the fact that as age of the child increases, the chance to join kindergarten would increase and hence may attribute to increased physical activity which ultimately would lead to increased metabolic activity and energy requirements.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the prevalence of overweight/obesity in the participating children was 16.1% [overweight (4.9%), obese (11.2%)]. The review of similar studies conducted in various countries demonstrated that while the prevalence of overweight / obesity in preschoolers varied between 4% and 21% in some studies, which was consistent with the results of the present study [4,5,9,[13][14][15][16][17] , it was lower in some studies [14][15][16][17] , and higher in some other studies [18,19] . For instance, the rate was higher in two studies conducted in Iran and Vietnam [35.7% [18] and 21% [20] respectively], and was lower in a study conducted in Cameroon [8% [16] ] than that in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to those of the studies conducted in Iraq [24] , Iran [18] and Kenya [19] . Children's watching television long hours not only prevents them from participating in physical activities adequately but also encourages them to consume sweet and salty foods [14,28] . One of the interesting results of the present study is that the children whose mothers were university graduates were more obese than were the others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study from southwest China identified a positive association between the DDS and increased risk of obesity among adults, which was attributed to excessive energy and deficient micronutrients, along with increasing dietary diversity. Consistent results were also found among preschool children in studies in southeast rural China (Lyu et al, ) and a city in Ethiopia (Sorrie et al, ). In this study, the high DDS was a significant predictor for increased risk of childhood overweight (Table ).…”
Section: Discussionsupporting
confidence: 77%
“…The DDS is a simple and quick indicator of dietary adequacy and is a predictor of improved nutritional status (Steyn, Nel, Nantel, Kennedy, & Labadarios, ). However, the DDS is also positively associated with obesity (Lyu et al, ; Sorrie, Yesuf, & Gebremichael, ). For example, a study from southwest China identified a positive association between the DDS and increased risk of obesity among adults, which was attributed to excessive energy and deficient micronutrients, along with increasing dietary diversity.…”
Section: Discussionmentioning
confidence: 99%